The cultural complex : contemporary Jungian perspectives on psyche and society - Singer, Thomas, 1942-; Kimbles, Samuel L. (Brunner-Routledge, 2004)
Based on Jung's theory of complexes, this book offers a new perspective on conflicts between groups and cultures, demonstrating how the effects of cultural complexes can be felt in the behaviour of disenfranchised groups across the world.